Tantalum and zirconium induced structural transitions at complex [111] tilt grain boundaries in copper. (15th May 2020) - Meiners, T.; Duarte, J.M.; Richter, G.; Dehm, G.; Liebscher, C.H.
Graphical abstract: Abstract: Alloying nanocrystalline copper (Cu) with immiscible elements, such as tantalum (Ta) and zirconium (Zr), is a promising technique to manipulate grain boundary properties and by this suppress grain growth at elevated temperatures. However, insights on the atomistic origins on the influence of impurity elements on grain boundaries are lacking. In this study, the atomistic effects of Ta and Zr on [111] tilt grain boundaries in Cu are investigated by high resolution scanning transmission electron microscopy techniques. In case of Ta, the formation of spherical, nano-scale precipitates in close vicinity to the grain boundaries is observed, but no sign of segregation. The particles induce a repelling force to migrating boundaries and act as local pinning points. The segregation of Zr is observed to occur either at confined grain boundary steps or homogeneously along the boundaries without steps. In both cases a strong disordering of the defect or grain boundary structure is revealed. Furthermore, at low Zr concentrations it induces structural grain boundary transitions and partial atomic reordering of the grain boundary structural units.